ПРИЧИНЫ ВОЗНИКНОВЕНИЯ НАРУШЕНИЙ БЕЗОПАСНОСТИ ДВИЖЕНИЯ ПОЕЗДОВ НА АО «УЗБЕКИСТАН ТЕМИР ЙУЛЛАРИ» - Валиев, М.Ш. (SCIENCE and SOCIETY, 2021)
Train safety is one of the main indicators when evaluating the work of railway transport. The article discusses the causes of train safety violations, provides a classification of technical equipment failures, the occurrence of which at different stages of existence is given special attention. A system for studying dangerous failures is also provided, which will help to identify dangerous failures in advance, while constant statistical processing can be performed in automatic mode, followed by modeling situations to prevent critical consequences associated with the occurrence of cases of train safety violations.